2010
DOI: 10.4103/0253-7613.64504
|View full text |Cite
|
Sign up to set email alerts
|

The antiepileptic effect of Centella asiatica on the activities of Na + /K + , Mg 2+ and Ca 2+ -ATPases in rat brain during pentylenetetrazol-induced epilepsy

Abstract: Background:To study the anticonvulsant effect of different extracts of Centella asiatica (CA) in male albino rats with reference to Na+/K+, Mg2+ and Ca2+-ATPase activities.Materials and Methods:Male Wistar rats (150±25 g b.w.) were divided into seven groups of six each i.e. (a) control rats treated with saline, (b) pentylenetetrazol (PTZ)-induced epileptic group (60 mg/kg, i.p.), (c) epileptic group pretreated with n-hexane extract (n-HE), (d) epileptic group pretreated with chloroform extract (CE), (e) epilep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 29 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…The neuroprotective effects of Centella asiatica have been well documented [20, 61-64], yet these effects have usually been attributed to the bioactive triterpenes (asiatic acid, madecassic acid, asiaticoside, madacassoside) present in the plant. We previously reported that our original extract of CAW does not contain these triterpenes [18].…”
Section: Discussionmentioning
confidence: 99%
“…The neuroprotective effects of Centella asiatica have been well documented [20, 61-64], yet these effects have usually been attributed to the bioactive triterpenes (asiatic acid, madecassic acid, asiaticoside, madacassoside) present in the plant. We previously reported that our original extract of CAW does not contain these triterpenes [18].…”
Section: Discussionmentioning
confidence: 99%
“…In another study [ 74 ], De Lucia et al reported anticonvulsant and sedative activities of the hydroalcoholic extract of C. asiatica in rats using elevated-plus labyrinth and PTZ-induced convulsion models, and the extract was also shown to exert low toxicity by chronic application with the LD 50 value of 675 mg/kg (b.w.). Anticonvulsant activity of the hexane, chloroform, ethyl acetate, water, and n -butanol extracts prepared from C. asiatica was determined using PTZ-induced convulsion model in male Wistar rats, and effect of the extracts was also searched on Na + /K + , Mg 2+ , and Ca 2+ -ATPase activity [ 75 ]. The results pointed out to an increase in activity of three types of ATPases in the extract-administered groups accompanied by anticonvulsant activity.…”
Section: Neuroprotective Activity Of C Asiaticamentioning
confidence: 99%
“…[ 6 ] Anti seizure activity may result from direct or indirect modulation of ATPase activity. [ 7 ] Centella asiatica inhibits the memory impairment induced by scopolamine through the inhibition of AChE. [ 8 ] BR-16A (Mentat), a formulation containing Centella asiatica proved for its antistress effects.…”
Section: Introductionmentioning
confidence: 99%